MODEL KOMUNIKASI LINTAS BUDAYA DALAM RESOLUSI KONFLIK BERBASIS PRANATA ADAT MELAYU DAN MADURA DI KALIMANTAN BARAT - Yohanes Bahari (Jurnal Ilmu Komunikasi, 2008)
The title of this study is The Cross Cultural Communication Model in Conflict Resolution Based On Customs in Malayan and Madurese, West Kalimantan. The aims of this study are to investigate: whatever of the Malayan and Madurese customs which can functioning as conflict resolution media; how are functioning process of that customs; and how the respons of West Kalimantan communities to the use of that customs. The research method used are ethnographic multiple side studies. The findings are the Malayan and Madurese customs which functioning as conflict resolution medium is the musyawarah custom.The musyawarah custom can resolution the small conflict only, whereas to resolution of the large conflict, ussualy obligate to the police.The musyawarah customs did by kepala desa or traditional management of Malayan and Madurese as soon as when the conflict happened. The musyawarah custom based and spritualited on Islam religi. The musyawarah custom has preventive function to avoid widely and to stopping conflict (to create peace). West Kalimantan communities (Malayan-Madurse and non Malayan-Madurese) can approve the use of musyawarah custom to be media of conflict resolution, but if conflict connecting with Dayak, the resolution must use Dayak customs.